Head circumference and anterior fontanel measurements in newborns - Rizal Agus Tiansyah; Irawan Mangunatmadja; Aman Pulungan (Paediatrica Indonesiana, 2012)
Background Head growth and anterior fontanel (AP) closureare passive processes in response to brain growth. The growthof the brain and skull starts in the third week of intrauterinegestation. roth processes run simultaneously as a part of integralgrowth, along 'With increasing gestational age, until postô€€¿birth.Measurement of head circumference (He) and AF in newbornsis done to determine if the brain and skull grew normally duringthe intrauterine period.Objectives To investigate the differences in He and AF sizebetween preterm and fullô€€¿term infants, and the relationshipbetween gestational age (GA) and birth weight (BW) to Heand AF size.Methods This was a descriptive analytic study on preterm andfullô€€¿term newborns. Measurement of HC and AF was conductedin three phases: just after birth, 1x24 and 2x24 hours of age.Analysis of HC and AF size differences between preterm and fullterm subjects was performed, as well as analysis of the correlationbetween GA and BW to HC and AF size.Results Two hundred fifty newborns completed the study. Therewere 180 fullô€€¿term and 70 preterm subjects. Median HC in fullô€€¿term and preterm male subjects were 34 cm (range 31ô€€¿37 cm)and 31 cm (27ô€€¿34 cm), respectively. Median HC in fullô€€¿termand preterm female subjects were 33 cm (31ô€€¿36 cm) and 32 cm(27ô€€¿3S.S cm), respectively. Median AF in fullô€€¿term and pretermmale subjects were 2.17 cm (1.0SA.6 cm) and 2.22 cm (1.3SA.Scm), respectively, and in fullô€€¿term and preterm female subjectswere 2.02 cm (lA.1S cm) and 2.22 cm (0.7SA cm), respectively.The HC of preterms were significantly lower than the fullterms(P<O.OOl), however the AF size was not different between these2 groups of newborns (P =0 .28). Correlation test between GA andBW to HC size revealed a positive correlation (r=0.620, P<O.OO 1and r=0.801, P<O.OOl, respectively), but not to AF size (r=ô€€¿ 0.06,pô€€ 0.279 and F- 0.049, Pô€€0.44, respectively).Concl usions We found that the HC size of pre terms wassignificantly lower than thefullterms, but no significant differencesÂ in AF size between the two groups. GA and BW were associatedwith HC size, but not associated to AF size. [paediatr lndones.2012;52:145-51].